2023
DOI: 10.1101/2023.06.01.543149
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural Insights into Regulation of Insulin Expression Involving i-Motif DNA Structures in the Insulin-Linked Polymorphic Region

Abstract: The insulin linked polymorphic region (ILPR) is a variable number of tandem repeats (VNTR) region of DNA in the promoter of the insulin gene that regulates transcription of insulin. This region is known to form the alternative DNA structures, i-motifs and G-quadruplexes. Individuals have different sequence variants of VNTR repeats and although previous work investigated the effects of some variants on G-quadruplex formation, there is not a clear picture of the relationship between the sequence diversity, the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 52 publications
2
10
0
Order By: Relevance
“…Ultimately, this could impact gene expression or alternative splicing events and finally promotes disease formation and progression. First of all, G4s are fairly sensitive to changes in concentrations of ions like potassium (96), or of the pH (97), but strikingly a recent preprint by Guneri and colleagues observed G-quadruplex and i-motif formation (non-B DNA structure formed opposite of a G4 on the C-rich strand) in the promoter of the insulin gene (98). Its expression is dependent on the formation of these non-B DNA structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, this could impact gene expression or alternative splicing events and finally promotes disease formation and progression. First of all, G4s are fairly sensitive to changes in concentrations of ions like potassium (96), or of the pH (97), but strikingly a recent preprint by Guneri and colleagues observed G-quadruplex and i-motif formation (non-B DNA structure formed opposite of a G4 on the C-rich strand) in the promoter of the insulin gene (98). Its expression is dependent on the formation of these non-B DNA structures.…”
Section: Discussionmentioning
confidence: 99%
“…Its expression is dependent on the formation of these non-B DNA structures. Moreover, it has been shown that pathologically high glucose concentrations formed a stable G4 and lead to significantly increased expression compared to normal glucose concentrations within a luciferase reporter assay (98). The link between G4s and cancer is well known.…”
Section: Discussionmentioning
confidence: 99%
“…Putative i-Motifs can be identified based on their sequence pattern (C ≥3 N 1–12 ) 3 C ≥3 where C represents cytosine and N represent any nucleotide (29,30). The classic approach to identify potential putative iM-forming sequences is to search complementary sequences of G4-forming sequences based on sequence pattern matching.…”
Section: Methodsmentioning
confidence: 99%
“…The classic approach to identify potential putative iM-forming sequences is to search complementary sequences of G4-forming sequences based on sequence pattern matching. This assumption and current approaches limit the identification of iMs with their different variations in C:C(+) formations and topologies compared to G4s (29,30). To overcome this limitation, we designed a general pattern for iM formation searching using directed graph traversal process.…”
Section: Methodsmentioning
confidence: 99%
“…i-Motifs are four-stranded DNA structures that are formed in sequences rich in cytosines in the adjacent unpaired DNA strand, just like the G-rich sequences form G4s . The two parallel stranded duplexes associate in a head-to-tail orientation within the i-motif upon the intercalation of the CC+ base pair (Figure A) . At low pH values, this structure is stabilized by the protonation of cytosines.…”
Section: High-ordered Nucleic Acid Structures At the Telomeresmentioning
confidence: 99%